Dinâmica de solitons em superfluidos holográficos - Santos, Victor Pereira do Nascimento (2010)
We numerically study the formation and dynamics of domain-wall-like topological defects in superfluids, using a (3+1)-dimensional abelian Maxwell-Higgs model, under the AdS/CFT correspondence. We obtain the bulk-boundary propagators, as well as the correlation functions on the boundary for a scalar field, both in massive and non-massive cases. If we impose that the fields depends only on a boundary coordinate and the bulk radial coordinate, we obtain in the dual theory the domain wall solutions found in literature. From these solutions we found that the superfluid is characterized by two length scales, one for the order parameter and other for the charge density. We also study the change of charge density in the region near the interface of the defect, and finally we investigate the modifications needed in theory to study the dynamics of these solutions.